Demonstration Of Introduction To Traditional Food Pudak, A Special Food From Gresik To Increase Children's Knowledge At RA Raden Paku Kedamean Gresik - Masturoh, Umi; Khasanah, Risky Surotul; Imamah, Nur; Afiyah, Nur; Febrianti, Elsa Nur; Azkiyah, Kasyifatul; Maulidina, Mazildha Nur (PUDAK: Local Wisdom Community Journal, 2025)
Early childhood education is a crucial initial stage in developing knowledge, attitudes, and skills. One way to instill an understanding of local culture from an early age is through the introduction of traditional foods. This study aimed to introduce Pudak, a traditional Gresik food, to students at RA Raden Paku Kedamean as a means of broadening their knowledge and preserving the culture. The method used was thematic learning through storytelling, direct observation, and simple practical exercises. The results showed that the children gained a better understanding of the characteristics of local food, learned about the basic ingredients of pudak, and fostered pride in their regional culture. Therefore, this study confirms that introducing traditional foods can be an effective learning strategy and a means of cultural preservation for the younger generation